The Visits of the Romanian Royal Family to the University of Cluj in the Interwar Period - Marius Mureșan (University Babes-Bolyai, 2021)
Shortly after the creation of Greater Romania, an ample process of administrative-territorial integration of the new provinces began, which became part of the Romanian state during 1918. As part of this process, higher education received an important role. The present article analyses the way in which the University of Cluj evolved, after the Romanian takeover of the Hungarian institution, focusing at the same time on the way in which the Royal House supported its development. Primary sources from the interwar period were used for the analysis, such as the "Universul" and the "Gazeta Transilvaniei" newspapers, respectively the yearbooks of the University of Cluj. The objective of the study is to reconstruct the visits paid by the Royal House to the University of Cluj, highlighting, through a quantitative analysis of the press releases, the development of festivities, the significance of the speeches and the evolution of the relations between the university and the monarchy. For the analysed period, i.e., 1918-1939, three visits of the Royal Family dedicated exclusively to university festivities were identified, the first one in 1920, when the inauguration celebrations took place, a second one in 1930, when the tenth anniversary of that event was celebrated, and a third one in 1937, when new spaces were opened for carrying out university activities.